Safety Assessment of Bacteroides uniformis CECT 7771 Isolated from Stools of Healthy Breast-Fed Infants. - M Leonor Fernández-Murga; Yolanda Sanz (PLoS ONE, 2016)
BACKGROUND:Bacteroides uniformis CECT 7771 is a potential probiotic strain, originally isolated from the stools of healthy breast-feed infants. The strain showed pre-clinical efficacy in a mouse obesity model. The objective of this study was to evaluate its potential toxicity and translocation ability after acute oral administration to mice. METHODS AND FINDINGS:A safety study was conducted in immunocompetent and immunosuppressed C57BL-6 mice. Both mouse groups (n = 10 per group) were fed orally 2 x 10(9) colony forming units (cfu)/day of B. uniformis CECT 7771 or placebo by gavage for 6 days. Throughout this time, feed and water intake and body weight were monitored. Afterwards, mice were sacrificed and biological samples were collected to analyze blood and urine biochemistry, inflammatory and immune markers; gut mucosal histology and bacterial translocation to peripheral tissues. The results demonstrated that acute ingestion of this Bacteroides strain had no adverse effects on the animals' general health status or food intake, nor did it affect biochemical indicators of liver, kidney and pancreatic function or gut mucosal histology. Findings also demonstrated that administration did not lead to bacterial translocation to blood, liver or mesenteric lymph nodes. B. uniformis CECT 7771 also downregulated gene and protein expression (iNOS and PPAR-γ) and inflammatory cytokines induced by immunosuppression. CONCLUSIONS:The findings indicate that the acute oral consumption of B. uniformis CECT 7771 does not raise safety concerns in mice. Further studies in humans should be conducted.